(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Biogas is a renewable fuel produced by the breakdown of organic materials such as food waste and animal manure. It may be used for a variety of things, including car fuel, heating, and power generation. Global warming and the greenhouse effect are caused by harmful chemicals emitted into the atmosphere. Emissions from automobiles and industry are one of the causes of global warming. Excessive use of fossil fuels, such as global warming, results in a shift in fuel supply. As a consequence, alternative fuels are crucial in replacing fossil fuels in order to ensure that fossil fuels are preserved for future generations. The goal of this study is to provide an overview of biogas production, including its advantages and disadvantages. The present research gives a detailed review of the prospective technologies for generating biogas as a source of sustainable energy. Biogas is a long-term, environmentally friendly energy source that mostly consists of methane and other gases. It will be extremely important in the next year since it does not release dangerous gases.